Analisis Pemetaan Profil Badan Usaha Milik Desa Serta Potensi dan Permasalahannya di Bidang Pengelolaan Air Bersih: (studi kasus di BUMDes Kertajaya, Cianjur, Provinsi Jawa Barat) - Hanny Hanny; Lidya Agustina; Ita Salsalina Lingga; Rapina Rapina; Yenni Carolina; Elyzabeth I Marpaung; Erna Erna; Herman Kambono; Lauw Tjun Tjun; Oktavianti Oktavianti; Enrico Goiyardi (Universitas Katolik Soegijapranata, 2020)
Based on comparison data between 2017 and 2018, according to BPS (Statistic Central Data) the number of the poverty rate decreases in the villages is much higher than in urban areas. The role of the government does not escape here through the Ministry of Village, Development of Disadvantaged Regions and Transmigration in terms of encouraging all villages to have Village-Owned Enterprises (BUMDes). Although the BUMDes program has been launched since 2010, previous research shows that the BUMDes implementation program still not optimal. Departing from this condition, this research in the context of community service was created with the aim of mapping the profile of BUMDes, as well as finding the potential and controlling BUMDes and related business units. Meanwhile the issuing BUMDes is Kertajaya BUMDes, Cianjur Regency, West Java Province, while the business unit issued is PAB Tirta Jaya which is engaged in the provision of clean water. BUMDes Kertajaya has various potentials in the fields of clean water, tourism, agriculture, facilities and fisheries. Our research indicate that BUMDes Kertajaya have good governance but still have constraints such as limited internet facilities, units business funding, human resources regeneration, minimum number of operating income and limited infrastructure facilities. While the potential PAB Tirta Jaya to develop its business in the field of clean water supply is quite high, especially in terms of raw materials and marketing. Some of the obstacles faced by PAB Tirta Jaya are the currently inadequate equipment available for business development / expansion, the lack of operating profit, the difficulty of PAB Kerta Jaya in regenerating human resources, the business value of the PAB Tirta Jaya that is currently underway is not yet high.